Oliver Twist - Dickens, Charles; McCaughrean, Geraldine (Oxford, Oxford University Press, 2001)
Embark on a riveting journey into the heart of 19th-century London with Charles Dickens's timeless classic, "Oliver Twist." First published in serial form between 1837 and 1839, this novel is a poignant exploration of social injustice, poverty, and the indomitable spirit of a young orphan navigating a world fraught with peril. The story follows the life of Oliver Twist, a poor orphan who endures the harsh conditions of a workhouse before finding himself thrust into the shadowy underworld of Victorian London. From the malevolent Fagin and his gang of juvenile delinquents to the benevolent Mr. Brownlow, the novel introduces a cast of characters that have become iconic in the annals of English literature.
Keywords: English fiction